Protection of Concurrent Creditors in PKPU against Bankrupt Debtors from the Perspective of Hifz Maal (A Case Study of PT Altha Medika Indonesia) - Siti Aisyah; Cahaya Permata (LP2M IAIN Palopo, 2026)
Concurrent creditors do not possess specific security rights, making their position the weakest in the distribution of a debtor's assets. This is reflected in the case of PT Altha Medika Indonesia, which experienced financial difficulties resulting in delays in payments to its creditors. In Decision Number 238/Pdt.Sus-PKPU/2024/PN.Niaga.Jkt.Pst., the debtor proposed a debt repayment scheme of 50% of the outstanding debt, with the remaining balance to be paid over a period of 60 months. However, the debtor failed to fulfill its payment obligations to the concurrent creditors. Consequently, the creditors filed a petition for the annulment of the composition agreement under Decision Number 63/Pdt.Sus-Pembatalan Perdamaian/2025/PN.Niaga.Jkt.Pst., which ultimately resulted in the debtor being declared bankrupt. This study aims to analyze the legal protection of concurrent creditors in PKPU, examine the regulation of legal protection for concurrent creditors in the case of PT Altha Medika Indonesia, and analyze it from the perspective of hifz maal. This research employs normative legal research using the statute approach, conceptual approach, and judicial case study approach. The data used are secondary data collected through library research and analyzed qualitatively using a descriptive-analytical method. The findings indicate that the legal protection of concurrent creditors in PKPU is provided through voting rights, the right to file objections, and the right to receive proportional payment. Nevertheless, such protection remains inadequate because concurrent creditors remain in a vulnerable position due to the absence of security rights and their dependence on the debtor's ability to fulfill its obligations. From the perspective of hifz maal, the protection of property, justice, and responsibility in fulfilling the rights of concurrent creditors are strongly emphasized.